PENGARUH LINGKUNGAN KERJA DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN DI RUMAH MAKAN SUBARI 74 LARANGAN - Triono, Freddy; Aditya, Michael Khrisna (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
This research aims to determine the influence of the work environment and work morale on employee performance at the Surabi 74 Larangan Restaurant, Tangerang City, Banten Province. This research uses a quantitative descriptive research approach with multiple analysis methods. The data collection technique was carried out by distributing questionnaires to respondents, using a Likert scale. The sampling technique used was saturated sampling, where the population and sample were the same, namely 34 employees of Rumah Makan Surabi 74 Larangan. Partial research results: work environment and work spirit influence employee performance at Rumah Makan Surabi 74 Larangan. The work environment at Rumah Makan Surabi 74 Prohibitions affect employee performance, including physical factors such as the condition of the work space, lighting, temperature, noise, cleanliness and comfort, but also include non-physical factors such as organizational culture, dynamics of interactions between colleagues, and implementation of management systems. Then work enthusiasm plays a role in improving performance by encouraging active employee participation, initiative, and improving the quality of services and products.